Thinkful of Icariin Induces Triple-Negative Breast Cancer Cell Apoptosis and Suppresses Invasion by Inhibiting the JNK/c-Jun Signaling Pathway [Letter] - Mariya SS; Rinendyaputri R; Nikmah UA (Dove Medical Press, 2023)
Sela Septima Mariya, Ratih Rinendyaputri, Uly Alfi Nikmah Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Cibinong, West Java, IndonesiaCorrespondence: Ratih Rinendyaputri, Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Jl. Raya Bogor No. 490, Cibinong – Bogor Km. 46, Cibinong, West Java, Indonesia, Email ratih.rinendyaputri@brin.go.id